2015
DOI: 10.1016/j.cmi.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of hepatitis C virus (HCV) is associated with lower quantitative hepatitis B surface antigen and higher serum interferon-γ-induced protein 10 levels in HBV/HCV-coinfected patients

Abstract: Different viral dominance patterns have been documented in coinfection with hepatitis B virus (HBV) and hepatitis C virus (HCV) based on HBV DNA and HCV RNA quantification. In most cases, HCV is dominant and suppresses HBV replication. In vitro studies revealed that there is most probably no direct interference between HBV and HCV replication. We hypothesized that indirect mechanisms mediated by host immune responses might be responsible for the different dominance patterns. In this study we analysed quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 37 publications
2
44
0
1
Order By: Relevance
“…We have not included the immune response in our model since there is little quantitative information about the immune response to the five viruses studied here, making it difficult to estimate the values of the extra parameters that would be necessary. Our model shows that viruses fundamentally interact through a competition for resources, but stimulating the immune response can potentially enhance or hinder the competitive advantage of one virus, with some studies suggesting that the immune response plays a role in viral interactions during coinfections [18,19,30,31].…”
Section: Limitations Of the Modelmentioning
confidence: 82%
See 1 more Smart Citation
“…We have not included the immune response in our model since there is little quantitative information about the immune response to the five viruses studied here, making it difficult to estimate the values of the extra parameters that would be necessary. Our model shows that viruses fundamentally interact through a competition for resources, but stimulating the immune response can potentially enhance or hinder the competitive advantage of one virus, with some studies suggesting that the immune response plays a role in viral interactions during coinfections [18,19,30,31].…”
Section: Limitations Of the Modelmentioning
confidence: 82%
“…Our key finding is that blocking of one virus infection by the presence of another can be explained simply through resource competition. Some studies have suggested that other mechanisms, such as the immune response [18,19,30,31] or interference through viral proteins [31,32] are responsible for the growth interference between two viruses. Our model does not include either of these mechanisms, suggesting that they are not necessary to explain the phenomenon.…”
Section: Implications Of Our Findingsmentioning
confidence: 99%
“…In particular, systematic reviews have shown that there is a significant clinical association between HCV and IR and/or type 2 diabetes, suggesting that HCV increases the risk of diabetes especially in predisposed individuals . To exclude confounding causes of steatosis, we excluded subjects with type 2 diabetes, although we still found that HBV‐HCV subjects had a lower prevalence of prediabetes than HCV subjects but similar to HBV subjects suggesting that HBV may interact with HCV by reducing IR as opposed to what is seen in HBV mono‐infection, although a viral interference, that is suppression of HCV replication by HBV, for example, through secretion of HCV‐induced cytokines, could also be involved. Further studies are warranted to assess this point.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, suppression or clearance of HCV infection with effective anti‐HCV therapy with either IFN‐ or DAA‐based therapy will remove the suppression on HBV replication and result in HBV reactivation. Recent cell culture studies further suggest that HCV suppresses HBV replication indirectly by way of IP‐10–related innate immune mechanism . In contrast to DAAs, IFN also exerts an inhibitory effect on HBV replication .…”
Section: Discussionmentioning
confidence: 99%